2022
DOI: 10.15388/omee.2022.13.73
|View full text |Cite
|
Sign up to set email alerts
|

sWOM and Online Shopping within a Disease Menace: The Case of Vietnam

Abstract: Although electronic word-of-mouth via social networking sites (or sWOM) greatly induced online shopping, its importance in shopping decisions during the coronavirus disease (COVID-19) pandemic has not been holistically considered. Based on the necessity of sWOM, uses and gratifications theory (UGT), and health belief theory (HBT), this study frames a consumer shopping tendency model toward sWOM in the context of the pandemic. A web-based survey was designed to collect data from 403 respondents who are inclined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Furthermore, Thomas et al (2019) demonstrated that information quantity negatively influences review credibility; thus, customers perceive a higher number of reviews for products as less trustworthy. However, the extant research supports that information quantity is a motivator of customers' willingness to purchase products via social media-based eWOM (Le and Chu, 2022). In the current context, "information quantity" indicates the amount of information that is available for products via chatbots.…”
Section: Research Framework and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Thomas et al (2019) demonstrated that information quantity negatively influences review credibility; thus, customers perceive a higher number of reviews for products as less trustworthy. However, the extant research supports that information quantity is a motivator of customers' willingness to purchase products via social media-based eWOM (Le and Chu, 2022). In the current context, "information quantity" indicates the amount of information that is available for products via chatbots.…”
Section: Research Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Concomitantly, information credibility triggers purchase intention. Though a great number of studies have examined these links in e-commerce and social media (Le and Chu, 2022;Thomas et al, 2019), only a few have considered information credibility as a motivation for purchase intention in the chatbot context. Earlier research revealed that information Inducing AI-powered chatbot use credibility positively affects purchase intention via online reviews (Zhang et al, 2014).…”
Section: Research Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Otherwise, WOM delineates a forwarding of information to people (Le and Chu, 2022). WOM is negative or positive in the literature of consumer complaints (Gelbrich and Roschk, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%